Antibiotic Resistance, Biofilm Formation, and Identification of FimH and FimA Adhesion Genes in Uropathogenic Escherichia Coli (UPEC) Isolated from Patients in Baghdad Province - Hamid, Safa A. Abdul; Khoshabeh, Ramina M. (Iraqi Journal of Science, 2024)
Urinary tract infections (UTIs) are one of the most common infectious disorders worldwide. The most frequent cause of UTIs is uropathogenic Escherichia coli (UPEC). The current study is designed to assess the resistance of antibiotics, the formation of biofilm, and the detection of adhesion genes in E. coli isolated from patients with UTIs. A hundred and fifty samples were collected from patients with confirmed UTIs in Baghdad province during the period of October 2022 to February 2023. Isolation and identification of E. coli were performed using cultural characteristics, gram staining, and biochemical examination, and the results indicated that 52 (35%) isolates were identified as E. coli. Eleven antibiotic discs were utilized to estimate the sensitivity of E. coli isolates. 98% of isolates were resistant to ampicillin, followed by 75.5% of isolates resistant to both trimethoprim/sulfamethoxazole and fosfomycin, followed by 73.5, 71.4, 67.3, 53.1, and 6.1% of isolates resistant to imipenem, ceftazidime, nitrofurantoin, cefepime, and amikacin. All isolates were sensitive to piperacillin-tazobactam, ciprofloxacin, and aztreonam at 100%, 100%, and 98%, respectively. The microtiter plate method was utilized to estimate the ability of E. coli to form biofilm. The majority of isolates (69.2%; n = 36) were moderate biofilm producers, while 19.2% (n = 10) and 11.5% (n = 6) of isolates were strong and weak biofilm producers, respectively. Polymerase Chain Reactions (PCR) were applied to determine the gene expression level of adhesion genes (fimH and fimA genes). Forty isolates harbored both fimH and fimA genes.